Building renovation at district level – Lessons learned from international case studies. (September 2021) - Rose, Jørgen; Thomsen, Kirsten Engelund; Domingo-Irigoyen, Silvia; Bolliger, Roman; Venus, David; Konstantinou, Thaleia; Mlecnik, Erwin; Almeida, Manuela; Barbosa, Ricardo; Terés-Zubiaga, Jon; Johansson, Erik; Davidsson, Henrik; et al.
Highlights: District scale renovation can achieve cost-efficiency while reducing both energy use and CO2 -emissions. Drivers for district renovation are not restricted to energy savings and emission reductions. Indoor climate, improving the overall building quality, image and value plays a key role for involved stakeholders. Available funding is the most decisive factor in carrying out district scale renovations. Abstract: Renovation at district scale is a key strategy to reduce CO2 emissions by optimising the implementation of renewable energy sources and taking advantage of economy of scale. This paper focuses on analysing good practice examples on energy renovations at district scale. The paper adapts a qualitative research methodology in four phases, including the multi-perspective analysis of nine exemplary renovation projects in six European countries, including identification of drivers and barriers of different stakeholders. It is found that the drivers for a district renovation are not restricted to energy savings, but typically also include improving the overall quality of life as well as the image and economic value of a district. Moreover, the need for financial models that can alleviate split-incentive problems between investors and resident organizations is identified. Barriers for carrying out a district renovation include that there is a need to comply with energy standards, that the renovation scope had to be limited to avoid a noticeable rent increase and that resettling of tenants during the renovation is often not possible. Lessons learned include that good communication amongst the different stakeholders, especially with residents, plays a key role for the success of the project. Furthermore, a strong leadership is needed to coordinate activities due to the great number of stakeholders.